Geostatistical analysis of strain localization in triaxial tests on sand. Issue 4 (3rd October 2019) - Salvatore, E.; Spacagna, R. L.; Andò, E.; Ochmanski, M.
Abstract : Strain localisation influences the behaviour of sheared soils in a way that the assumption of the continuum loses validity and may become inapplicable. This occurrence affects the interpretation of triaxial tests where samples are usually considered as representative elements of an equivalent continuum and a phenomenological interpretation is carried out to calibrate constitutive models. Considering the inherent and stress-induced heterogeneity of the material as a possible precursor of localisation, the evolution of porosity and strain fields is studied interpreting with statistical and geostatistical analyses, the results of X-ray computerised microtomography. The study is performed on sandy samples sheared in triaxial compression and extension. The analysis carried out before shearing shows a meaningful statistical heterogeneity of the porosity with correlation lengths to the order of a few grain diameters. The evolution on shearing reveals the onset of a second statistical population and of an anisotropic spatial variation dictated by strain localisation.